Witches and Wizards in Lithuanian Mythological Tales and their Equivalents in Russian and English - Gimževskienė, Karolina (Vertimo studijos, 2018)
[full article and abstract in Lithuanian; abstract in English] This article aims to find cultural equivalents for a group of Lithuanian mythological creatures, namely, magical people, including wizards, witches, sorcerers, etc. in English and Russian languages. Therefore, first, different sources of folkloric translation and its specific issues were consulted, which created the possibility for discussion of some cultural aspects as well as links between Lithuanian, Slavic and Celtic folklore. Second, a comparative analysis of the named mythological creatures in Lithuanian, Russian and English languages and cultures was carried out. The results of the analysis have shown which names of these creatures might be considered exact cultural equivalents and which of them are only partial analogs. Such information is useful not only when choosing a domestication strategy, but for a foreignization strategy as well because these equivalents can be used both in the translation text itself and in additional extratextual comments. The conclusions given at the end of this article and the provided table, where specific translation suggestions are given, may be of practical importance for translators or authors writing about Lithuanian mythology and folklore for English or Russian speaking readers.